PORTFOLIO AS AN ALTERNATIVE OF LANGUAGE ASSESSMENT - Eriza - - (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2013)
Portfolio is a formative assessment which aims to  monitor students’ learning achievement by selecting the collection of studensts’ work. Unlike the summative assessment which summarizes students’ achievement through one test taking, portfolio assessment is conducted continously over a semester. This article presents the concepts of portfolio assessment. It also dicusses how to implement portfolio assessment in the classroom.